Social and Institutional Delegitimization in Latin American Populist Regimes from the Late 20th to Early 21st Century - Francesco Davide Ragno (Confluenze, 2025)
The construction of the enemy's image in Latin American populist regimes extends beyond political opponents, encompassing social actors and institutions. This essay examines such representations within populist movements and leaders—such as Peru’s Fujimori, Argentina’s Menem and Kirchner, and Venezuela’s Chávez—active in the 1990s and early 21st century. Common features emerge across these populist regimes, particularly in identifying social enemies and institutional adversaries.